2008
DOI: 10.1053/j.ajkd.2008.02.301
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Impaired Olfactory Function in ESRD to Malnutrition and Retained Uremic Molecules

Abstract: Background-Olfactory function is impaired in patients with end stage renal disease (ESRD) and may contribute to uremic anorexia. Only limited correlations of olfactory function and nutritional status have been reported. This study examined the relationship of impaired olfactory function to malnutrition and levels of the retained uremic solutes monomethylamine, ethylamine, indoxyl sulfate, and P-cresol sulfate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 35 publications
7
41
0
7
Order By: Relevance
“…This association was observed in women but not in men, and it persisted after adjusting for age, socio-demographic factors (education, living status, and receipt of pension payment), and BMI. Full enjoyment and appreciation of food flavors require an intact olfactory system [26]; hence, it is not surprising that nutritional problems are important sequelae of olfactory dysfunction that can occur with the aging process [27]. Our study findings supports this observation, as it showed that older adults with moderate/severe versus normal olfactory impairment had poorer diet quality in the longer term, after accounting for potential confounders.…”
Section: Discussionsupporting
confidence: 83%
“…This association was observed in women but not in men, and it persisted after adjusting for age, socio-demographic factors (education, living status, and receipt of pension payment), and BMI. Full enjoyment and appreciation of food flavors require an intact olfactory system [26]; hence, it is not surprising that nutritional problems are important sequelae of olfactory dysfunction that can occur with the aging process [27]. Our study findings supports this observation, as it showed that older adults with moderate/severe versus normal olfactory impairment had poorer diet quality in the longer term, after accounting for potential confounders.…”
Section: Discussionsupporting
confidence: 83%
“…It remains unknown whether the measurement of other olfactory characteristics, such as detection thresholds, perceived intensity or liking, would have revealed a similar result since this is the first study of smell function in children with CKD. In contrast, adults with severe CKD have been reported to have a reduced ability to identify odours, based on the results of odour identification and discrimination tests [7,8], and odour threshold tests [9,30]. Not all adults with CKD have changes in olfactory function.…”
Section: Olfactionmentioning
confidence: 99%
“…Not all adults with CKD have changes in olfactory function. For example, in a study of 8 7 0 3 ARB 1 4 0 0 Mycophenolate 1 0 0 3 Cyclosporine 1 2 0 1 Tacrolimus 1 0 0 3 Azathioprine 0 1 0 1 Sirolimus 1 1 0 0 Prednisolone 3 5 0 8 Atenolol 1 3 0 0 Atorvastinin 3 2 0 1 patients with end stage renal disease, the odour identification ability of the least malnourished patients was no different to that of controls [30]. Clearly, differences in testing methodology, patient age and severity of CKD make it difficult to adequately compare the findings-not only between studies, but also between adults and children.…”
Section: Olfactionmentioning
confidence: 99%
“…In a small study, no relation could be found between four retention solutes (monomethylamine, ethylamine, indoxyl sulfate, and p-cresol sulfate) and either olfactory discrimination or global assessment of nutrition (36). All of these studies have used assays targeted for specified solutes.…”
Section: Epidemiologic Association Of Solutes With Outcomesmentioning
confidence: 99%